Development of and invasive mosquito surveillance and management strategy in Cyprus - Vasquez Christodoulou, Marlen (My University, 2026)
Vasquez MI, Violaris M, Development of and invasive mosquito surveillance and management strategy in Cyprus, 2nd Meeting of the FAO/IAEA Technical Cooperation Project RER5022 Establishing Genetic Control Programmes for Aedes Invasive Mosquitoes, Chania, Greece, 18-20 December 2017.